Elementary School Mathematics Learning Strategies: An Empirical Study Analysis - Rahayu Fitriani; Juliana Artatib; Haeruddin Azhari (LOGIKA: Jurnal Pendidikan Matematika, 2025)
This study aims to analyze various mathematics learning strategies in elementary schools that have been developed and empirically tested over the past five years, to provide a comprehensive overview of their trends, effectiveness, and relevance to 21st-century learning needs. This is due to the low mathematical literacy achievements of Indonesian students in PISA, TIMSS, and the National Assessment, which indicates that the dominance of conventional teacher-centered methods remains an obstacle in developing critical thinking, creativity, and problem-solving skills. The research method used was a Systematic Literature Review (SLR) with reference to the PRISMA guidelines. The search process was conducted in the Google Scholar database with specific keywords and focused on articles indexed SINTA 1-5, published between 2020-2025, and containing empirical data in the context of elementary mathematics learning. Of the 1,600 identified articles, five articles were screened that met the inclusion criteria and were further analyzed. The results showed that innovative learning strategies consistently improve learning outcomes, motivation, and higher-order thinking skills. The traditional game-based GASING method has been proven to increase motivation and conceptual understanding, the TGT model assisted by Articulate Storyline strengthens student interest and engagement, the integration of ethnomathematics with Augmented Reality encourages problem-solving and critical thinking skills, the environment-based STAD connects mathematics with real contexts, while PBL assisted by manipulative media deepens the understanding of abstract concepts. Therefore, it can be concluded that innovative, contextual, collaborative, and technology-based mathematics learning strategies are the answer to the numeracy achievement gap in elementary schools. The combination of concrete and digital media, integration of local contexts, and collaboration-based learning has the potential to reduce the achievement gap between students while improving the quality of elementary mathematics education in Indonesia